Contemporary ijtihad an analysis of individual and collective approaches - Yusri Mohamad (Islamic and Strategies Studies Institute Berhad, 2016)
This book examines ijtihad in its contemporary mannifestation with the premise that there is a need to delimit the boundaries and framework of this process to reduce dispute and alow for focus on more strategic aspects of ijtihad.The earlier parts of this book focus on prevalent views on the main principles, components and element of ijtihad while analyzing possible changes and modifications to the theory and practice of ijtihad. There main findings if this study are that a substantial amount of the controversies surroundings ijtihad goes back to terminological difference and that the divide between contending trends may be narrowed down to reasonable degress. Utilizing these findings,the author went to highlight ideal approaches and suggest improvements for contemporary ijtihad in general and to the selected samples covered in this study.